MRI and ultrasound in diagnosis and management of rheumatological diseases - Brindle, Kathleen [ (Kathleen A.)]; Katz, James D. (Annals of the New York Academy of Sciences, 2009)
Inflammatory Arthritis may encompass a rapidly destructive disorder of joints with associated systemic manifestations. The advent of disease modifying therapeutics that promise to halt rheumatoid arthritis (RA) disease progression has escalated the clinical importance of early diagnosis and subsequent assessment of remission.